Effect of Supplemental Enzyme on Nutrient Digestibility and Performance of Broiler Chicks Fed on Diets Containing Triticale - Pourreza, J.; Samie, A.H.; Rowghani, E. (International Journal of Poultry Science, 2007)
The influence of enzyme supplementation on performance and digestibility of dry matter and protein in young broiler chicks was examined for a diet based on triticale supplemented with different levels of enzyme. In a completely randomized design, two hundred d-old chicks (Ross strain) were divided into 20 groups, ten chicks per group. A basal diet containing 65% triticale was supplemented with zero, 100, 200, 400 and 800 g/kg enzyme and given to four replicates for 21 days. Added enzyme (xylanase) improved (P< 0.05) body weight, body weight gain, feed intake and feed conversion ratio. Apparent digestibilities of energy and protein were increased (P< 0.05) due to supplemental enzyme. Non-significant improvement was observed in protein and energy efficiencies by the addition of enzyme. All improvements had a similar trend and were the highest at 200 g/kg enzyme supplementation. Higher levels of enzyme had no beneficial effect on measured criteria. The results indicated that the nutritional value of cereal grains such as triticale can be improved by supplemental enzyme containing mainly xylanase to the diet of young broiler chicks.